The Relationship Of Early Provision of Complete Asi Foods (mp-asi) With The Incident of Diarrhea in Babies Aged 0-6 Months at The Atikah Sipolu Clinic- Polu District Panyabungan City Districtchristmas Mandailing Year 2023 - Desi, Ferika (International Journal of Medicine And publich Health, 2024)
Babies aged 0-6 months can grow optimally by relying on exclusive breastfeeding for the first 6 months of life, after 6 months of age the baby is given complementary foods. Complementary Foods (MP-ASI) are foods or drinks that contain nutrients that are given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. The condition of the digestive system of babies aged 0-6 months the size of the stomach is still small and the digestive system is not yet fully developed, therefore babies aged 0-6 months are only able to consume breast milk. This study aims to determine the relationship between complementary feeding of breast milk ( mp-asi) early with the incidence of diarrhea in infants aged 0-6 months, Panyabungan District, Mandailing Natal Regency, Christmas in 2023. The type of research used is a descriptive study with a cross sectional approach The population in the study is mothers who have a baby 0-6 months in the midwife clinic atikah sipolu-Polu . The sampling technique uses Total Sampling with a sample size of 35 people. Data collection by using primary and secondary data. Data analysis using the chi -square test with a significant level of p<0.05). The results of the analysis showed that there was a relationship between complementary feeding of breast milk ( MP-ASI) Early with the incidence of diarrhea in infants aged 0-6 months with a value of P = 0.002 where P = <0.05. It is hoped that the results of this study can add information for the community, especially mothers, about the relationship between early breastfeeding (MP-ASI) and the incidence of diarrhea in babies after 0-6 months.